2009
DOI: 10.1007/s00436-009-1682-8
|View full text |Cite
|
Sign up to set email alerts
|

Precocity of Gnathostoma turgidum in naturally infected four-eyed opossum Philander opossum pallidus from Temascal, Oaxaca, Mexico

Abstract: Two female advanced third-stage larvae of Gnathostoma turgidum recovered from the liver of one naturally infected four-eyed opossum Philander opossum pallidus collected in Oaxaca, Mexico, were morphologically examined. Because of some characteristics, the larvae do not fit into the typical advanced third-stage. The body shows a size at least three times larger than expected and rows of spines only in the anterior part of the body surface. Consequently, in this research, we document for the first time the preco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, preliminary studies of the helminths of the animals mentioned above were negative for this parasite. Almeyda-Artigas et al (2010) reported finding individuals of Philander opossum Linnaeus 1758, a species found on the island, infected with G. turgidum in Mexico, but no studies of this possible host have been made.…”
Section: Poeciliopsis Gracilismentioning
confidence: 99%
“…However, preliminary studies of the helminths of the animals mentioned above were negative for this parasite. Almeyda-Artigas et al (2010) reported finding individuals of Philander opossum Linnaeus 1758, a species found on the island, infected with G. turgidum in Mexico, but no studies of this possible host have been made.…”
Section: Poeciliopsis Gracilismentioning
confidence: 99%